THE ROLE OF URBAN FARMING TO HOUSEHOLD FOOD SECURITY IN THE SURAKARTA CITY, INDONESIA - Umi Barokah; Wiwit Rahayu; Ernoiz Antriyandarti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2023)
Urban areas are densely populated areas, so that land for agricultural production is minimal. The city of Surakarta is the center of the economy in the Soloraya region, whose agricultural land area continues to decrease. The study aimed to analyze household food security and the role of urban farming on household food security. The data used in the research was primary data collected by interview, recording, observation, and food recall methods. Respondent to the research consists of 60 households that carried out urban farming in 5 districts (Pasar Kliwon, Jebres, Banjarsari, Laweyan, Serengan) in Surakarta. The analytical data used food security analysis with indicators of food expenditure and energy consumption levels and descriptive analysis for urban farming to household food security. The results showed that as many as 21 or (35.00%) were categorized as food secure households, 12 or (20.00%) were classified as food vulnerable households, 22 or (36.67%) were categorized as lack of food households, and 5 (8, 33%) was categorized as food insecure. The role of urban farming on household food security is indicated by its contribution to food expenditure of Rp 87,336.00 or 7.69% to total food expenditure per month. It is necessary to increase the role of urban farming in household food security both in increasing income and providing food for households. This can be done, among other things, by intensifying and diversifying urban farming businesses.